The complaint handler’s bind: How organisational constraints lead to defensive responses to criticism - Alex Gillespie; Tom Reader (PLoS ONE, 2025)
Defensiveness is often implicated in systemic organisational failures to explain why early warning signs were ignored and organisational resilience was compromised. But how does an organisation become defensive? We propose that defensiveness can arise as a response to contradictory work demands. Our research focuses on UK hospital staff tasked with responding to criticism online (herein complaint handlers). We examine these responses to criticism using a mixed methods explanatory sequential design. Six defensive tactics were reliably identified: redirecting patients to other channels, evading issues, psychologising concerns, invalidating concerns as incomplete, closing the feedback episode, and individualising concerns with bespoke workarounds. These defensive tactics were generally associated with less organisational learning and were sometimes viewed as unhelpful. To explain these results, we introduce the complaint handler’s bind: staff are tasked with responding to complaints without a viable pathway for organisational learning and an implicit injunction against voicing this dilemma. This demand-control double bind unwittingly gives staff little alternative but to be defensive. Future research, we conclude, needs to conceptualise defensiveness as sometimes a symptom rather than a cause of problems in organisational learning.